Antara Cinta, Iman, dan Keluarga: Pernikahan Dini Secara Siri dan Keputusan Berpindah Agama - Heru Syahputra; Muhammad Zul Fahmi; Ahmad Rifaldi Siregar; Afri Wulan Sari; Desinta Fitriani Simatupang (Pusat Riset dan Inovasi Nasional, 2024)
Early marriage conducted through siri (unregistered religious marriage) remains a complex social phenomenon in Indonesia, often influenced by emotional ties, religious beliefs, and family expectations. This study explores the intersection between love, faith, and family in shaping decisions surrounding early siri marriage and religious conversion. Through a qualitative approach, the research examines how young individuals navigate personal relationships while facing moral, spiritual, and cultural pressures. The findings reveal that early siri marriage is frequently chosen as a solution to preserve family honor or legitimize romantic relationships, yet it also creates legal and psychological vulnerabilities, especially for young women. Furthermore, the decision to convert religions is shown to be deeply connected to marital commitments and familial influence, reflecting the struggle between personal conviction and social acceptance. This study highlights the need for broader legal protection, education, and social support systems to address the long-term impacts of unregistered early marriage and religious transition. Ultimately, the research emphasizes that decisions regarding marriage and faith are rarely individual choices alone, but rather shaped by powerful emotional and familial dynamics.